Deep Learning Quick Reference : Useful hacks for training and optimizing deep neural networks with TensorFlow and Keras. - Bernico, Michael (Packt Publishing, 2018)
This book is a practical guide to applying deep neural networks including MLPs, CNNs, LSTMs, and more in Keras and TensorFlow. Packed with useful hacks to solve real-world challenges along with the supported math and theory around each topic, this book will be a quick reference for training and optimize your deep neural networks.